A novel mutation in COL4A1 gene: A possible cause of early postnatal cerebrovascular events. (23rd February 2015) - Decio, Alice; Tonduti, Davide; Pichiecchio, Anna; Vetro, Annalisa; Ciccone, Roberto; Limongelli, Ivan; Giorda, Roberto; Caffi, Lorella; Balottin, Umberto; Zuffardi, Orsetta; Orcesi, Simona
Abstract : COL4A1 is located in humans on chromosome13q34 and it encodes the alpha 1 chain of type IV collagen, a component of basal membrane. It is expressed mainly in the brain, muscles, kidneys and eyes. Different COL4A1 mutations have been reported in many patients who present a very wide spectrum of clinical symptoms. They typically show a multisystemic phenotype. Here we report on the case of a patient carrying a novel de novo splicing mutation of COL4A1 associated with a distinctive clinical picture characterized by onset in infancy and an unusual evolution of the neuroradiological features. At three months of age, the child was diagnosed with a congenital cataract, while his brain MRI was normal. Over the following years, the patient developed focal epilepsy, mild diplegia, asymptomatic microhematuria, raised creatine kinase levels, MRI white matter abnormalities and brain calcification on CT. During the neuroradiological follow‐up the extension and intensity of the brain lesions progressively decreased. The significance of a second variant in COL4A1 carried by the child and inherited from his father remains to be clarified. In conclusion, our patient shows new aspects of this collagenopathy and possibly a COL4A1 compound heterozygosity. © 2015 Wiley Periodicals, Inc.